The Winter of Our Discontent - Steinbeck, John, 1902-1968 (London Pan Books, 1970)
Steinbeck's story set in small-town New England early in the century. Its inhabitants include Ethan Hawley, to whom the rat-race beckons enticingly, Marullo, a razor-sharp Sicilian store owner, and Marge, a good-time girl, alluring in body, warped in soul.
Keywords: Conduct of life -- Grocery trade--Employees -- United States